Ethical teachings of Abū Ḥāmid al-Ghazālī : economics of happiness - Al-Daghistani, Sami, 1986- (Anthem religion and society series, 2021)
This book studies the interplay of economic philosophy and moral conduct as reflected in the writings of one of the most renowned scholars in Islamic history, Abū Ḥāmid al-Ghazālī (d. 1111). Al-Ghazālī contributed to Islamic theology, philosophy, and Sufism but is also regarded as one of the forerunners of classical economic thought in Islamic tradition.